Slower Lower Limb Blood Pooling Increases Orthostatic Tolerance in Women with Vasovagal Syncope - Skoog, Johan; Zachrisson, Helene; Länne, Toste; Lindenberger, Marcus (Frontiers in Physiology, 2016)
Background and Aim: Slower lower limb blood pooling and associated blunted sympathetic activation has been detected in healthy women prone to orthostatic syncope. Whether these findings are true also for patients with vasovagal syncope (VVS) is unknown. The aim was to investigate initial blood pooling time (poolingtime, time to 50% of total blood pooling) together with hemodynamic responses and orthostatic tolerance during lower body negative pressure (LBNP) in VVS and healthy controls. Methods and Results: Fourteen VVS women (25.7±1.3 years) and fifteen healthy women (22.8±0.8 years) were subjected to single-step and graded LBNP to pre-syncope. Lower limb blood pooling (ml ∙ 100 ml-1), poolingtime (sec), hemodynamic responses and LBNP-tolerance were evaluated. LBNP induced comparable lower limb blood pooling in both groups (controls, 3.1± 0.3; VVS, 2.9 ± 0.3 ml ∙ 100 ml-1, P = 0.70). In controls, shorter poolingtime correlated to higher LBNP-tolerance (r=-0.550, P<0.05) as well as better maintained stroke volume (r=-0.698, P<0.01) and cardiac output (r=-0.563, P<0.05). In contrast, shorter poolingtime correlated to lower LBNP-tolerance in VVS (r=0.821, P<0.001) and larger decline in stroke volume (r=0.611, P<0.05). Furthermore, in controls, shorter poolingtime correlated to baroreflex-mediated hemodynamic changes during LBNP, e.g., increased vasoconstriction (P<0.001). In VVS, poolingtime was not correlated with LBNP-induced baroreceptor unloading, but rather highly correlated to resting calf blood flow (P<0.001). Conclusions: Shorter poolingtime seems to elicit greater sympathetic activation with a concomitant higher orthostatic tolerance in healthy women. The contrasting findings in VVS indicate a deteriorated vascular sympathetic control suggesting well-defined differences already in the initial responses during orthostatic stress.